MULTIMODALITY IN THE SPREAD OF VASECTOMY PROGRAM IN SURABAYA CITY - Wono, Hilda Yunita (Universitas Mercu Buana, 2024)
One of the regions in Indonesia with the highest number of poor people and a significant growth rate is in East Java Province. According to data, East Java has 4.181 million poor people with a population of 40.67 million people. The capital of East Java Province, Surabaya City is recorded to have the densest population. This population growth rate is the task of the Surabaya City DP3APPKB to overcome it and one of the programs is vasectomy. Surabaya in 2013 once received an award for fostering a vasectomy group until the acceptor was high, but after that the number of acceptors continues to decline drastically until now. The purpose of this study was to find opinions related to multimodality in the spread of vasectomy programs. This can provide input to the DP3APPKB service. This research was conducted with a qualitative approach in order to get input from various points of view in depth. Qualitatively finding that visuals on brochures are a concern, important cadres are convincing and multimodal is still needed.